(untitled) (Mongolian Journal of Agricultural Sciences, 2014)
Mumie contains humid and fulvic acids. For this study, pure mumie was fractionated into fulvic acid (FA) and humic acid (HA) fractions. Humic and Fulvic Acids are highly active bioregulators, and also they contain both macro- and micro-nutrients needed by human and animal bodies. Mumie is stone like material found in Mongolia at higher altitude, which has various medical applications in Mongolia and other Asian countries [2,3]. In the present study, the biological activity of mumie and its fractions was measured. Fractions were prepared according to the protocol described by I. A. Scheretkin and A.I. Khlebnikov. Both humic and fulvic acids can be obtained with the yields of 5.3% and 18.6 % respectively DOI: http://dx.doi.org/10.5564/mjas.v11i2.213 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.33-35